Fingerprinting Sediment Transport in River‐Dominated Margins Using Combined Mineral Magnetic and Radionuclide Methods. Issue 8 (8th August 2018) - Wang, Jinlong; Zhang, Weiguo; Baskaran, Mark; Du, Jinzhou; Zhou, Feng; Wu, Hui
Abstract: Both magnetic properties and radionuclides are widely used to trace sediment transport in aquatic environments; however, these methods have not been used in combination. In this study, the East China Sea (ECS), a typical river‐dominated margin, was chosen to demonstrate the advantages of combining these two methods to track sediment movements on a seasonal to annual timescale. The ratios between saturation isothermal remnant magnetization and anhysteretic remnant magnetization (χARM /SIRM) and 7 Be/ 210 Pbex activity ratios as well as mass balance of 7 Be provide information on the seasonal transport of sediment from the Changjiang Estuary to the neighboring shelf. Both 210 Pb budget and SIRM distribution in the inner shelf of the ECS show that a small fraction (at most 14% of annual Changjiang sediment discharge) of particles could be transported offshore. Most of 7 Be activities in inner shelf sediments of the ECS were below detection limit due to relatively lower residence times and dilution by the older sediment. The observation that radionuclide activities exhibit a better correlation with χARM /SIRM ratios than with grain size suggests that iron oxides are the primary carriers of 7 Be, 210 Pb, and 234 Th. The absorption of radionuclides onto magnetic minerals further reinforces the reliability of this combined approach in tracing sediment transport. Our study indicates that radionuclides, with different half‐lives, can be utilized for quantifying sediment dynamics, whereas magnetic properties can yield more detailed information on sediment transport directions. The combined analysis of magnetic parameters and radionuclides offers a better understanding of sediment transport in river‐dominated areas. Key Points: The 7 Be/ 210 Pbex and χARM /SIRM ratios of surface sediments in the estuary region of the East China Sea varied seasonally Both 210 Pb budget and SIRM data suggest that only a fraction of particles could be transported out of the inner shelf of the ECS A combined analysis of radionuclides and magnetic properties offers a better understanding of sediment transport in river‐dominated margins